Penegakan Hukum terhadap Tindak Pidana Penghinaan dan Pencemaran Nama Baik - Minarti Usman; Roy Marthen Moonti; Ibrahim Ahmad (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2026)
Criminal acts of insult and defamation are acts that attack a person's honor and reputation, either directly or through electronic media. This study aims to analyze the legal provisions and law enforcement for criminal acts of insult and defamation in the Criminal Code and Law Number 1 of 2024 concerning Electronic Information and Transactions (ITE Law). The research method used is normative legal research with a statutory regulatory approach and literature review. The results indicate that defamation is regulated by Article 433 of the Criminal Code and Article 27A of the ITE Law, while law enforcement is carried out through investigation, inquiry, prosecution, and court hearings. In practice, law enforcement still faces obstacles in the form of differing interpretations, difficulties in proving digital evidence, and limited facilities and capabilities of law enforcement officers. Therefore, it is necessary to increase the capacity of law enforcement officers and increase public legal awareness to achieve effective law enforcement in the digital era.